Heavy metals contamination in water, sediments and fish of freshwater ecosystems in Pakistan. Issue 5 (20th April 2022) - Afzaal, Muhammad; Hameed, Saman; Liaqat, Iram; Ali Khan, Amir Amanat; abdul Manan, Hafiz; Shahid, Raja; Altaf, Muhammad
Abstract: Freshwater ecosystems are being contaminated by heavy metal pollution. The primary source of contamination is wastewater discharged from urban, industrial, and agricultural facilities. The contaminated water contains hazardous amounts of heavy metals mixed in the freshwater ecosystem, causing deleterious impacts on marine life and humans. This review paper highlights the contamination of the freshwater ecosystem of Pakistan with heavy metals. Heavy metals' concentration in sediments, water, and fish were assessed in the food chain, and their relationship with sites and sources was explored. It was observed that heavy metals present in freshwater and sediments bio-accumulate into fish organs. It was also found that some parts of freshwaters such as the rivers Ravi, Chenab, Kabul, and Indus were highly contaminated, and they imposed negative impacts on fish and human health. The River Ravi, receiving a huge amount of industrial and sewage wastewater from urban centers and industries of Central Punjab, was highly contaminated compared to other rivers of Pakistan. The ecosystem health of River Indus was the best among all the rivers of Pakistan due to the enormous volume of water flow and less number of industrial units along with it. Freshwater fish of the rivers Indus, Chenab, and Jhelum are consumable for humans. The presence of heavy metals also causes social, environmental, and economic problems. Therefore, the wastewater should be treated before discharge into freshwater streams and rivers to lessen the harmful impacts of heavy metals on marine life and human beings. HIGHLIGHTS: The freshwater ecosystems of Pakistan are highly contaminated with heavy metals. The rivers Ravi and Kabul are highly contaminated because of discharge of industrial and sewage water. The rivers Chenab and Jhelum have moderate metal contamination at a few sites. The River Indus is very less contaminated with heavy metals. Contaminated fish from polluted rivers can badly impact human health. Graphical Abstract